Deep near-infrared spectroscopy of passively evolving galaxies at z≳1.4 - Onodera, M; Renzini, A; Carollo, M; Cappellari, M; Mancini, C; Strazzullo, V; Daddi, E; Arimoto, N; Gobat, R; Yamada, Y; McCracken, H; Ilbert, O; et al. (2012)
We present the results of new near-IR spectroscopic observations of passive galaxies at z ≳ 1.4 in a concentration of BzK-selected galaxies in the COSMOS field. The observations have been conducted with Subaru/MOIRCS, and have resulted in absorption lines and/or continuum detection for 18 out of 34 objects. This allows us to measure spectroscopic redshifts for a sample that is almost complete to K AB = 21. COSMOS photometric redshifts are found in fair agreement overall with the spectroscopic redshifts, with a standard deviation of 0.05; however, 30% of objects have photometric redshifts systematically underestimated by up to 25%. We show that these systematic offsets in photometric redshifts can be removed by using these objects as a training set. All galaxies fall in four distinct redshift spikes at z = 1.43, 1.53, 1.67, and 1.82, with this latter one including seven galaxies. SED fits to broadband fluxes indicate stellar masses in the range of 4-40 × 10 10 M and that star formation was quenched 1Gyr before the cosmic epoch at which they are observed. The spectra of several individual galaxies have allowed us to measure their HδF indices and the strengths of the 4000 Å break, which confirms their identification as passive galaxies, as does a composite spectrum resulting from the co-addition of 17 individual spectra. The effective radii of the galaxies have been measured on the COSMOS HST/ACS i F814W-band image, confirming the coexistence at these redshifts of passive galaxies, which are substantially more compact than their local counterparts with others that follow the local effective radius-stellar mass relation. For the galaxy with the best signal-to-noise spectrum we were able to measure a velocity dispersion of 270 ± 105kms-1 (error bar including systematic errors), indicating that this galaxy lies closely on the virial relation given its stellar mass and effective radius. © 2012 The American Astronomical Society. All rights reserved.